A COMPARATIVE STUDY OF LINGUAPOETIC ELEMENTS IN THE IN WORKS OF JACK LONDON AND ABDULLA QODIRIY (International journal of artificial intelligence, 2025)
Language and culture are inseparable phenomena. Linguoculturology studies how linguistic units reflect the worldview, mentality, and traditions of a particular nation. In literature, this interconnection manifests through artistic and linguistic devices that carry cultural meanings. Both Abdulla Qodiriy, a pioneer of modern Uzbek prose, and Jack London, a representative of American naturalism, vividly express the cultural and social essence of their nations through their language and style.